2020
DOI: 10.1186/s13287-020-01754-z
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNA LINC00314 facilitates osteogenic differentiation of adipose-derived stem cells through the hsa-miR-129-5p/GRM5 axis via the Wnt signaling pathway

Abstract: Background: Many studies have shown that long noncoding RNAs (lncRNAs) are closely related to the stimulation of osteogenic differentiation of adipose-derived stem cells (ADSCs) and the prevention of osteoporosis. Current research aimed to investigate the novel lncRNA and explored the function and molecular mechanism of the LINC00314/miR-129-5p/GRM5 axis in regulating osteogenic differentiation of ADSCs. Methods: LncRNA and miRNA sequencing was performed in normal and osteogenic differentiation-induced ADSCs (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 33 publications
1
17
0
Order By: Relevance
“…MicroRNA inhibited the translation of target gene by binding to its 3′ UTR region ( Lai, 2002 ). In Shi et al’s (2020) study, hsa-miR-129-5p inhibited Wnt/β-catenin pathway via targeting Grm5 . In Li et al (2013) ; Zhang et al (2017) , and Cao et al (2018) , hsa-miR-129-5p inhibited Wnt/β-catenin pathway via targeting Apc , Sox4 , and Wnt5a , respectively.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…MicroRNA inhibited the translation of target gene by binding to its 3′ UTR region ( Lai, 2002 ). In Shi et al’s (2020) study, hsa-miR-129-5p inhibited Wnt/β-catenin pathway via targeting Grm5 . In Li et al (2013) ; Zhang et al (2017) , and Cao et al (2018) , hsa-miR-129-5p inhibited Wnt/β-catenin pathway via targeting Apc , Sox4 , and Wnt5a , respectively.…”
Section: Discussionmentioning
confidence: 90%
“…miR-129-5p is a miRNA that has been reported as a regulator of cancer development and Alzheimer disease ( Li G. et al, 2019 ; Zeng et al, 2019 ). Shi et al found hsa-miR-129-5p inhibited osteogenic differentiation of adipose-derived stem cells ( Shi et al, 2020 ), while its function on bone formation is still unexplored. To further reveal the correlation between miR-129-5p and osteoporosis, in this study, we have stimulated aging-related osteoporosis in male aging mice model and menopause osteoporosis in female aging menopause mice model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have confirmed that several miRNAs can influence the osteogenic differentiation of ADSCs, such as miR-145-5p [ 17 ], miR-143-3p [ 18 ], and miR-129-5p [ 5 ]. Wang et al [ 19 ] reported that overexpression of miR-346 could regulate the Wnt/β-catenin signaling pathway by targeting GSK3b to promote the differentiation of BMSCs into osteoblasts.…”
Section: Discussionmentioning
confidence: 99%
“…ADSCs can play the function of multidirectional differentiation and self-renewal, and can differentiate into osteoblasts, chondrocytes, adipocytes, nerve cells, and myoblasts under different conditions [ 5 , 6 ]. In addition, ADSCs also have the advantages of easy access, simple sampling, minimally invasive, abundant sources, and relatively small immune rejection [ 7 ].…”
Section: Introductionmentioning
confidence: 99%